Effect of maraviroc on non-R5 tropic HIV-1: refined analysis of subjects from the phase IIb study A4001029. (January 2015) - Surdo, M.; Alteri, C.; Puertas, M.C.; Saccomandi, P.; Parrotta, L.; Swenson, L.; Chapman, D.; Costa, G.; Artese, A.; Balestra, E.; Aquaro, S.; Alcaro, S.; et al.
Abstract: We characterized maraviroc susceptibility of dual/mixed tropic viruses from subjects enrolled onto phase IIb study A4001029. Maraviroc baseline plasma samples from 13 multidrug-experienced subjects were sequenced and the HIV-1-env gene cloned into pNL4.3Δenv to obtain recombinant viruses. The V3 region was sequenced by the Sanger method and ultradeep sequencing. By analysing subjects having a weighted optimized background therapy susceptibility (wOBT) score of <1, 3/7 subjects were characterized by good in vivo and in vitro response to maraviroc therapy. Molecular docking simulations allowed us to rationalize the maraviroc susceptibility of dual/mixed tropic viruses. A subset of subjects with dual/mixed tropic viruses responded to maraviroc. Further investigations are warranted of CCR5 antagonists in subjects carrying dual/mixed tropic virus that explore the feasible use of maraviroc in subjects that is potentially larger than those infected with a pure R5 virus.